682. The Changing Epidemiology of Bacterial Meningitis During 2015–2017 in Turkey: A Hospital-Based Prospective Surveillance Study. (26th November 2018) - Ceyhan, Mehmet; Ozsurekci, Yasemin; Bayhan, Cihangül; Gurler, Nezahat; Sali, Enes; Emiroglu, Melike Keser; Öz, Fatma Nur; Camcioglu, Yıldız; Salman, Nuran; Kurugol, Zafer; Akisoglu, Havva Ozlem Altay; Tuygun, Nilden; et al.
Abstract: Background: The etiology of bacterial meningitis in Turkey has been changed after the implementation of conjugated vaccines against Streptococcus pneumonia and Haemophilus influenzae type b (Hib) in Turkish national immunization schedule. Methods. This prospective study was conducted in 25 hospitals located seven regions of Turkey (representing 30% of Turkey population) and children aged between 1 month and 18 years with suspected meningitis and hospitalized were included. Cerebrospinal fluid samples were collected and bacterial identification was made according to the multiplex PCR assay results. Results. During the study period, 927 children were hospitalized for suspected meningitis and Hib ( n :1), S. pneumonia ( n :17) and Neisseria meningitidis ( n :59) were detected in 77 samples (Figure 1, Table 1). During 2015–2016, N. meningitidis serogroup W, B, A, Y, X frequencies were as 5 (13.9%), 16 (44.4%), 1 (2.8%), 1 (2.8%), 1 (2.8%), respectively. There were 12 nongroupable N. meningitidis samples and serogroup C was not detected. In 2017, of meningococcal meningitis serogroup B, W, A, Y and X were identified in two (8.7%), 15 (65.2%), two (8.7%), 1 (4.3%) and 1 (4.3%) cases, respectively (Figure 2). There were four deaths in this study period, all of them were caused by N. meningitidis serogroup B and three of them were under 1 year old. Conclusion. The epidemiology of meningococcal diseases has been varied in time with or without any apparent reasons. Hajj is a well-known cause for serogroup W epidemics and serogorup W was the most common cause of meningitis in Turkey during 2009–2014 as in other Middle East countries. After the impact of serogroup W epidemics related to Hajj seen in 2010's was diminished, serogroup B has been leading cause of childhood meningitis since 2015. In countries affected from Hajj like Turkey, vaccination of children with serogroup B meningococcal vaccine as well as quadrivalentconjugated vaccine seems to be very important. It should be kept in mind that meningococcal epidemiology is dynamic and needed to be closely monitored to detect changes in years Disclosures: All authors: No reported disclosures.